'We are fed up' – encountering the complex German call for sustainable, small-scale agriculture. Issue 2 (23rd February 2020) - Nowack, Wiebke; Hoffmann, Harry
ABSTRACT: The German agrarian opposition, a broad societal movement consisting of farmers and diverse civic groups with origins in the 1980s, has established a new tradition. Since 2011, the movements' coordinating organizations annually initiate large-scale demonstrations in Berlin entitled 'We are fed up.' It provides a platform for critical voices and public protests regarding the prevailing agri-food system and implemented agricultural policies. By analysing insights as well as qualitative interviews with involved actors, this contribution outlines why the 'We are fed up'-demonstrations appear to be a deeply rooted rather than short-term phenomenon, thus providing a unique case of an agriculture and food movement in the Global North.